Fryns Syndrome Associated with Recessive Mutations in PIGN in two Separate Families. Issue 7 (6th May 2016) - McInerney‐Leo, Aideen M.; Harris, Jessica E.; Gattas, Michael; Peach, Elizabeth E.; Sinnott, Stephen; Dudding‐Byth, Tracy; Rajagopalan, Sulekha; Barnett, Christopher P.; Anderson, Lisa K.; Wheeler, Lawrie; Brown, Matthew A.; Leo, Paul J.; et al.
Abstract : We identified mutations in PIGN in two siblings and one unrelated individual diagnosed with Fryns syndrome. Mutations in PIGN have been previously shown to cause multiple congenital anomalies syndrome and a single case of syndromic diaphragmatic hernia was also reported. There is no apparent correlation between the location of the mutations and diagnosis but our review suggests that mutation type may play a role where two protein‐truncating alleles are associated with the more severe phenotype of Fryns syndrome/syndromic diaphragmatic hernia. ABSTRACT: Fryns syndrome is an autosomal recessive condition characterized by congenital diaphragmatic hernia (CDH), dysmorphic facial features, distal digital hypoplasia, and other associated malformations, and is the most common syndromic form of CDH. No gene has been associated with this condition. Whole‐exome sequence data from two siblings and three unrelated individuals with Fryns syndrome were filtered for rare, good quality, coding mutations fitting a recessive inheritance model. Compound heterozygous mutations in PIGN were identified in the siblings, with appropriate parental segregation: a novel STOP mutation (c.1966C>T: p.Glu656X) and a rare (minor allele frequency <0.001) donor splice site mutation (c.1674+1G>C) causing skipping of exon 18 and utilization of a cryptic acceptor site in exon 19. A further novel homozygous STOP mutation in PIGN (c.694A>T: p.Lys232X) was detected in one unrelated case. All three variants affected highly conserved bases. The two remaining cases were negative for PIGN mutations. Mutations in PIGN have been reported in cases with multiple congenital anomalies, including one case with syndromic CDH. Fryns syndrome can be caused by recessive mutations in PIGN . Whether PIGN affects other syndromic and non‐syndromic forms of CDH warrants investigation.